Brand Origin as a Mediation Variable in Social Media Marketing Activities Influences Purchase Decisions in Pempek Yuk Paka Culinary Business - Campaka, Miselia; Roosdhani, Mohamad Rifqy; Arifin, Samsul (Raudhah Publisher, 2024)
This study investigates social media marketing activities on purchasing decisions for traditional culinary businesses that sell traditional food of one region in another area. In addition, this study also investigates the mediation role of Brand Origin from this culinary business on purchase decisions. This study used a survey of 212 samples, taken from customers who had made at least one purchase. The results of this valid survey were then collected and analyzed using PLS-SEM modeling. This study found that if only social media marketing activities do not have a significant effect on purchase decisions, but if this social media marketing activity is carried out at the same time as Brand Origin eating, it will have a significant effect on purchase decisions.